Ramipril Prior to Thrombolysis Attenuates the Early Increase of PAI-1 in Patients with Acute Myocardial Infarction - Wagner, Andreas; Herkner, Harald; Schreiber, Wolfgang; Bur, Andreas; Woisetschläger, Christian; Stix, Günther; Laggner, Anton N.; Hirschl, Michael M. (Thrombosis and Haemostasis, 2002)
In a placebo-controlled, double-blinded, randomized study we evaluated the effect of ramipril prior to thrombolysis on the course of PAI-1 plasma levels and on the frequency of postinfarct ischemic events in patients with acute myocardial infarction. Fifty-one out of 99 patients received 2.5 mg ramipril orally prior to thrombolysis and 12 h later. The blood samples for determination of PAI-1 plasma levels were collected on admission and 2, 4, 8, 12 and 24 h after thrombolysis. Postinfarct ischemic events were registered until coronary angiography was performed and defined as recurrent chest pain and/or evidence of ischemic signs on the ECG (ST-depression or ST-segment elevation of 1 mm in one or more inferior or anterior leads). Coronary angiography was performed within 7 days after the onset of myocardial infarction. Patients were classified into two groups: those without reperfusion of the infarct-related artery (TIMI grade 0 or 1) and those with reperfusion of the infarct-related artery (TIMI grade 2,3). On admission, PAI-1 plasma levels were similiar in both groups (ramipril: 47.1 [4.8] ng/ml; placebo: 49.1 [4.8] ng/ml). The PAI-1AUC was 77.2 [6.7] ng/ml/h in the ramipril group and 95.4 [6.2] ng/ml/h in the placebo group (p = 0.013). Significant differences between groups were observed at 4, 8 and 12 h after thrombolysis (4 h: 85.5 (11.3) vs. 116 (12.3) ng/ml, p < 0.01; 8 h: 79.1 (11.2) vs. 100.9 (9.3) ng/ml, p < 0.01; 12 hrs: 71.3 (9.5) vs. 87.4 (7.7) ng/ml, p < 0.05). The relative frequency of postinfarct ischemic events was significantly lower in the ramipril group (2.5% versus 7.1%, p = 0.001). Additionally, we observed a significant higher rate of TIMI grade 2 and 3 of the infarct-related artery in patients receiving oral ramipril compared to the placebo group (73% versus 54%; p = 0.035).Our study demonstrates a favorable effect of ramipril on the fibrinolytic system after thrombolysis associated with a lower rate of postinfarct ischemic events within the first days after myocardial infarction. Therefore, the application of ramipril prior to thrombolysis appears to be a reasonable concomitant treatment which may reduce early infarctrelated complications.
Keywords: Ramipril; thrombolysis; myocardial infarction